5‐Unsubstituted Pyrido[3, 2, 1‐jk]carbazol‐6‐ones: Syntheses, Substitution, and Cyclization Reactions. (5th May 2014) - Stadlbauer, Wolfgang; Dang, Van Hoai; Guttenberger, Nikolaus
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>